Patterns of Brain Injury in Newborns Treated with Extracorporeal Membrane Oxygenation - Wien, M.A.; Whitehead, M.T.; Bulas, D.; Ridore, M.; Melbourne, L.; Oldenburg, G.; Short, B.L.; Massaro, A.N. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Neonates treated with extracorporeal membrane oxygenation are at risk for brain injury and subsequent neurodevelopmental compromise. Advances in MR imaging and improved accessibility have led to the increased use of routine MR imaging after extracorporeal membrane oxygenation. Our objective was to describe the frequency and patterns of extracorporeal membrane oxygenation–related brain injury based on MR imaging findings in a large contemporary cohort of neonates treated with extracorporeal membrane oxygenation.MATERIALS AND METHODS: This was a retrospective study of neonatal patients treated with extracorporeal membrane oxygenation from 2005–2015 who underwent MR imaging before discharge. MR imaging and ultrasound studies were reviewed for location and type of parenchymal injury, ventricular abnormalities, and increased subarachnoid spaces. Parenchymal injury frequencies between patients treated with venoarterial and venovenous extracorporeal membrane oxygenation were compared by χ2 tests.RESULTS: Of 81 neonates studied, 46% demonstrated parenchymal injury; 6% showed infarction, mostly in vascular territories (5% anterior cerebral artery, 5% MCA, 1% posterior cerebral artery); and 20% had hemorrhagic lesions. The highest frequency of injury occurred in the frontal (right, 24%; left, 25%) and temporoparietal (right, 14%; left, 19%) white matter. Sonography had low sensitivity for these lesions. Other MR imaging findings included volume loss (35%), increased subarachnoid spaces (44%), and ventriculomegaly (17% mild, 5% moderate, 1% severe). There were more parenchymal injuries in neonates treated with venoarterial (49%) versus venovenous extracorporeal membrane oxygenation (29%, P = .13), but the pattern of injury was consistent between both modes.CONCLUSIONS: MR imaging identifies brain injury in nearly half of neonates after treatment with extracorporeal membrane oxygenation. The frontal and temporoparietal white matter are most commonly affected, without statistically significant laterality. This pattern of injury is similar between venovenous and venoarterial extracorporeal membrane oxygenation, though the frequency of injury may be higher after venoarterial extracorporeal membrane oxygenation.CUScranial ultrasoundECMOextracorporeal membrane oxygenationVAvenoarterialVVvenovenous